Analysis of trait-based variation in bovine exposure to viral respiratory tract infections at the wildlife-livestock interface in the Mnisi communal farming area of South Africa - Jansen van Vuuren, M. (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.